Biogas residue biochar shifted bacterial community, mineralization, and molecular structure of organic carbon in a sandy loam Alfisol. Issue 5 (16th March 2021) - Zheng, Xuebo; Dong, Jianxin; Zhang, Wenhui; Xiang, Jian; Yin, Xingsheng; Han, Lanfang
ABSTRACT: Pyrolysis into biochar as a soil amendment has been treated as an eco‐friendly and environmentally sustainable method to recycle biogas residue (BR). However, the effect of BR biochar on soil bacterial community, mineralization, and structure of organic carbon (OC) remains unrevealed, which limits the soil application of BR biochar. This study performed a microcosm incubation experiment for a sandy soil with BR and BR‐derived biochar produced at relatively low (300°C) and high (600°C) temperature (BC300 and BC600), and explored the shift in bacterial community, mineralization, and structure of OC. Results showed that BR decreased the richness and diversity of bacterial community by 19.0%–28.0%, while BR biochar caused lower reduction (4.0%–7.0%), suggesting the potential of pyrolysis in mitigating the harmful effect of BR in bacterial community. Fourier‐transform ion cyclotron resonance mass spectrometry and 13 C nuclear magnetic resonance demonstrated that BR and BR biochar shifted dissolved OC toward components with 12.0%–26.0% higher molecular weight and 18.0%–21.0% more aromatics but 10.0%–22.0% lower polarity and less protein‐, carbohydrate‐, and tannin‐like species, with the shift extent being stronger for BC600. Furthermore, BC600 increased the aromaticity of bulk OC but reduced the carbohydrate, possibly due to more  Actinobacteria genera. Additionally, BR significantly elevated the amount and rate of soil carbon mineralization, while the potentially mineralizable C was the lowest in the BC600‐treated soil. These findings suggested that the pyrolysis into biochar at high temperature would be a promising way to treat BR in terms of soil bacterial community richness/diversity and carbon sequestration. Abstract : Pyrolysis into biochar has been treated as an environmentally sustainable method to recycle biogas residue (BR). However, the effect of BR biochar on soil bacterial community, mineralization, and structure of organic carbon (OC) remains unrevealed. This study performed a microcosm incubation experiment for a sandy soil with BR and BR‐derived biochar produced at relatively low and high temperatures, and explored the shift in bacterial community, mineralization, and structure of OC. The findings suggested that the pyrolysis into biochar at high temperature would be a promising way to treat BR in terms of soil bacterial community richness/diversity and carbon sequestration.